Introduction of Early Spiritual Awareness in The Family Room - Zubaedah, Siti; Hafidz, Nur; Nurbaiti, Amalia (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
Every child born has the potential for goodness, namely the will to grow a sense of self-potential, the need to know, and be aware of the existence of God who created them. Communication that is built will bring out a commendable attitude and always side with virtue. These are the characteristics of the potential for spiritual awareness that contains high human values. The values of wisdom and making coverage always present the deep meaning and value of early childhood in their actions. The introduction of spiritual awareness can be used as a means or tool to activate the potential of children's spiritual intelligence in addition to their emotional and intellectual. From here, it is important to examine the introduction of spiritual awareness for early childhood starting in the family room. The goal is to introduce early childhood spiritual awareness through Islamic dimensions (faith, Islam, and ihsan) in every aspect of children's spiritual development in the family room. This research method uses descriptive qualitative by taking seven samples of Purwokerto families, seven families that teach, apply, and reflect on as well as families that have succeeded in being aware of the spiritual intelligence of early childhood through various Islamic activities. Data collection techniques using interviews, observation, and documentation with an active participation model. The results of the study show that the introduction of spiritual awareness from early childhood through, (1) Spiritual Awareness with a Sense of Love, the family introduces spirituality with a democratic parenting pattern that is not too authoritarian and permissive; (2) Spiritual Awareness with Morals, the family exemplifies good morals to children through daily activities; (3) Spiritual Awareness with Diversity, the family teaches basic worship; (4) Spiritual Awareness with Sincerity, educating a sense of sincerity to children also requires continuous sincerity, practice, and understanding so that children are sincere in studying and sincere in worship. These four points, children get kindness by growing a sense of awareness of humanity, a sense of God, and nature